Thiamine Deficiency Neuropathy in a Patient with Malnutrition due to Melancholic Depression - Rihene Melki; Rim Ben Soussia; Houcem Elomma Mrabet; Walid Bouali; Lazhar Zarrouk (Case Reports in Psychiatry)
Introduction. Melancholic depression is a daily clinical reality in psychiatry. It is a therapeutic emergency that can jeopardize life if not promptly and adequately treated. Apart from its high suicidal risk, complications related to the under-nourishment state are to be feared. Case Presentation. A 36-year-old woman was admitted with depressive symptoms, significant weight loss, and total functional impotence. Laboratory investigations revealed severe thiamine (vitamin B1) deficiency. An electromyography confirmed a sensory axonal neuropathy involving all four extremities suggesting a deficiency origin. Discussion. Vitamin and mineral deficiencies have been described in patients with malnutrition resulting from psychiatric illness (anorexia nervosa, eating disorders, severe depression, etc.). Thiamine is an essential cofactor in several biochemical pathways. Its deficiency can lead to neuropsychiatric morbidity. Conclusion. In our case, the rapid weight loss facilitated a cascade of complications related to nutritional deficiencies. Based on our clinical observations and the literature, thiamine deficiency should be considered in the presence of malnutrition and vulnerability, both on an organic and psychiatric level.